PENGARUH KEPUASAN KOMUNIKASI TERHADAP KINERJA PENDIDIK IPDN JATINANGOR - Yani Tri Wijayanti; Asep Suryana; Mien Hidayat (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2015)
Humans as social creatures are always interacts each others, including when they are within an organization. All activities that are conducted within an organization need an effective communication. Organizational communication is a process of delivering a massage to all elements within an organization. In this case, organizational communication has a signifiant role in creating an effective organization. The fulfilment of the needs of information and communication in an organization will increase the productivity of its employees. This study focuses on IPDN Jatinangor, an educational institution. When social interactions that include social contact and communication run well, the relationship among elements within the institution is also effectively kept. This situation eventually will increase the productivity of the institution in realizing the main goals of the institution